The Realization of Second Language Learning Strategies in the Newest Revision of 2013 Curriculum - Azza Azkiya (Journalistics: Journal of English Teaching and Applied Linguistics, 2023)
For decades, English teaching and learning in Indonesia have been through a number of changes and revision of curriculum. One of which was widely and extensively used was the 2013 curriculum in which all the aspects of learning has been provided inside of it. Unfortunately, teachers recently have neglected the importance of second language acquisition (SLA) in their activity. In this paper, the researcher investigated the relationship between SLA learning strategies with the newest revision of 2013 curriculum. The focus of the study was the curriculum document in the form of its lesson plan created by a teacher. The document was compared with O’Malley and Chamot’s topology of learning strategies (1990). The researcher also had an interview session with the teacher in charged in one of junior high schools in Ambal, Kabupaten Kebumen. The result showed that teacher didn’t consider the importance of SLA as the result of overwhelming administration duty. On the other hand, O’Malley and Chamot’s learning strategies is dominantly reflected in the curriculum. However, the well-support resources didn’t give much contribution to students’ achievement. Therefore, there should be evaluation and improvement from both parties involved in language learning.